A numerical evaluation of global oceanic emissions of α-pinene and isoprene - Luo, G.; Yu, F. (Atmospheric chemistry and physics, 2010)
A numerical evaluation of global oceanic emissions of α-pinene and isoprene based on both "bottom-up" and "top-down" methods is presented. We infer that the global "bottom-up" oceanic emissions of α-pinene and isoprene are 0.013 TgC yr−1 and 0.32 TgC yr−1, respectively. By constraining global chemistry model simulations with the shipborne measurement of Organics over the Ocean Modifying Particles in both Hemispheres summer cruise, we derived the global "top-down" oceanic α-pinene source of 29.5 TgC yr−1 and isoprene source of 11.6 TgC yr−1. Both the "bottom-up" and "top-down" values are subject to large uncertainties. The incomplete understanding of the in-situ phytoplankton communities and their range of emission potentials significantly impact the estimated global "bottom-up" oceanic emissions, while the estimated total amounts of the global "top-down" oceanic sources can be influenced by emission parameterizations, model and input data spatial resolutions, boundary layer mixing processes, and the treatments of chemical reactions. The global oceanic α-pinene source and its impact on organic aerosol formation is significant based on "top-down" method, but is negligible based on "bottom-up" approach. Our research highlights the importance of carrying out further research (especially measurements) to resolve the large offset in the derived oceanic organic emission based on two different approaches.